Shifting Frontiers of Theobroma Cacao: Opportunities and Challenges for Production (IntechOpen eBooks, 2024)
Cacao (Theobroma cacao L.) is a sacred tree and noble resource from South America. The Mayans and other early civilizations in Central America used cacao beans as tokens, which were subsequently transported to Europe to nurture monarchies and elites. Based on the discovery of cacao’s commercial potential and attributes, new cocoa plantations were established in other parts of the world, including Africa, Asia, and the Caribbean. Thus, cocoa has become an important cash crop in Africa, Central and South America, and Asia, where it is a major foreign exchange earner, industrial raw material, support for livelihood, and ecosystem services provision. Based on its global importance, there has been an increased need for the expansion of cultivation to meet the rising demand for cacao beans. Global environmental change, including climate change, variability, and weather extremes, has established new environmental boundaries with implications for area suitability for cocoa production and sustainability. Efforts to unlock the potentials of the established environmental boundaries may be built on the development and adoption of agrotechnological practices and integration of climate resilience for harnessing opportunities and potentials of the new environment, and thus, extension of the frontiers of cacao cultivation to meet the increasing global demand for cocoa beans. This book, “Shifting Frontiers of Theobroma Cacao - Opportunities and Challenges for Production” presents a comprehensive perspective of the interactions of changing environmental conditions, cocoa production, and sustainability. The book illuminates the challenges climate change presents for cocoa production and sustainability. It provides insights into the need for cocoa actors within the cocoa sector to strengthen climate mitigation and resilience building and to come to grips with the realities, magnitude, and inevitable persistence of climate challenges to cocoa production and sustainability.